Hokkaido, Japan: Jomon-Kultur auf Hokkaido - Wagner, Mayke (e-Forschungsberichte des DAI, 2023)
On Hokkaido Island, the northernmost island cluster of the Japanese archipelago, humans started to make clay vessels already about 9000 years BC. However, their use of pottery was not related to sedentary lifestyle and crop cultivation only started several millennia later. Hunter-gatherer communities with specialization on coastal seafood were common until historical periods, even until very recent times. The trajectory from use and management of natural resources to food production seems very different from what we know of other world regions. The aim of our research is to find out under which environmental and climate conditions the earliest inhabitants of Northern Japan developed which strategies of resource utilization. Networks of good exchange and ritual monuments receive special attention.